NUMERICAL ASSESSMENT TO HARVEST RAINWATER THROUGH CORE CUTS ON A FLAT ROOF - Shah, S.M.H. (Research Laboratory in Subterranean and Surface Hydraulics, University of Biskra, 2022)
An approach of rainwater harvesting (RWH) collected from the roof of a building provides the practical and effective utilization of rainwater which would ensure the availability and sustainable management of water. Instead of flat slabs, architects have designed attic and inverted slabs, which can serve the purpose of rainwater catchments and allow water to fall into dedicated catchment areas. Herein, the approach of rainwater collection through the core-cut method on a flat slab was analyzed on FLOW-3D based on the mean annual rainfall data of Karachi city, Pakistan. The results of the numerical simulation ensured that the developed harvesting system had the capability to capture and deliver the collected water into the storage tank. It has been noticed that between time 0 and 54 seconds, the value of the volume flow rate was 0, which indicated that the rainwater took time to accumulate prior to flowing into the cuts. After t = 54 seconds, a sudden increment in the volume flow rate was observed. This was due to the rainwater that accumulated on the roof and started to go through the cuts. However, after t = 70 seconds, the volume flow rate became steady and very minor fluctuations in the flow rate were noticed. Â© 2022 Shah S.M.H. and al.